ISLAMISATION IN SOUTH SULAWESI: REVIEW OF HISTORICAL PHILOSOPHY PERSPECTIVE SPECULATIVE AND CRITICAL (International Conference on Social and Islamic Studies, 2022)
This article examines the Islamization of South Sulawesi in the perspective of speculative and critical philosophy of history. The established order towards Islamization often gives rise to speculations that are believed by the people, without being based on a critical historical reconstruction. The established findings on Islamization were made by three preachers namely, Datuk ri Bandang, Datuk Patimang, Datuk ri Tiro who came from Lontara. However, there are other findings as an antithesis, especially those which find that Islam first spread in Tosora-Wajo brought by descendants of the Hadramaut named Sayyid Jamaluddin Akbar Alhusaini who came from Aceh, who traveled with a group of 15 people sourced from archaeological evidence and oral tradition. Islam that has reached the king, seems to ignore the narrative about Islam that grows in society. The impression is that history favors power based on writing, and ignores the history of societies based on archaeological evidence and oral traditions. It is known that Islamic values ​​in the Wajo community had developed before the arrival of Islam from Gowa. These two views will be dissected in a speculative and critical view. This article uses historical methods, performs heuristics in the form of lontara documents and archaeological evidence of Islamization in South Sulawesi, then critiques the sources used to reduce bias between the two views on Islamization, after which it is interpreted and historiographical.